Protein kinase D2 controls cardiac valve formation in zebrafish by regulating histone deacetylase 5 activity - Just, Steffen; Berger, Ina Maria; Meder, Benjamin; Backs, Johannes; Keller, Andreas; Marquart, Sabine; Frese, Karen S.; Patzel, Eva; Rauch, Gerd-Jörg; Katus, Hugo; Rottbauer, Wolfgang (Circulation, 2011)
Background— - - The molecular mechanisms that guide heart valve formation are not well understood. However, elucidation of the genetic basis of congenital heart disease is one of the prerequisites for the development of tissue-engineered heart valves. - - Methods and Results— - - We isolated here a mutation in zebrafish, bungee (bngjh177), which selectively perturbs valve formation in the embryonic heart by abrogating endocardial Notch signaling in cardiac cushions. We found by positional cloning that the bng phenotype is caused by a missense mutation (Y849N) in zebrafish protein kinase D2 (pkd2). The bng mutation selectively impairs PKD2 kinase activity and hence Histone deacetylase 5 phosphorylation, nuclear export, and inactivation. As a result, the expression of Histone deacetylase 5 target genes Krüppel-like factor 2a and 4a, transcription factors known to be pivotal for heart valve formation and to act upstream of Notch signaling, is severely downregulated in bungee (bng) mutant embryos. Accordingly, the expression of Notch target genes, such as Hey1, Hey2, and HeyL, is severely decreased in bng mutant embryos. Remarkably, downregulation of Histone deacetylase 5 activity in homozygous bng mutant embryos can rescue the mutant phenotype and reconstitutes notch1b expression in atrioventricular endocardial cells. - - Conclusions— - - We demonstrate for the first time that proper heart valve formation critically depends on Protein kinase D2-Histone deacetylase 5-Krüppel-like factor signaling.
Gesehen am 06.07.2022